The relationship between postpartum depression and lower maternal confidence in mothers with a history of depression during pregnancy - Arante, Flavia O. (Psychiatr Q, 2020)
BACKGROUND: The objective of the present study is to evaluate the association of postpartum depression and low maternal confidence in a sample of women who had depression during pregnancy. METHODS: Cross-sectional study performed from 2013 to 2015 with 346 postpartum women who had participated in an intervention to treat their depression during pregnancy. This study used the Maternal Confidence Questionnaire and the Patient Health Questionnaire 9-item scale. The prevalence ratio, adjusted and non-adjusted, and the 95% CI were calculated using Poisson regression with robust variance. Multivariate models estimated the Prevalence Ratios between postpartum depression and low maternal confidence adjusted for socio-demographic variables and maternal characteristics. Statistical analysis was performed with the STATA12. RESULTS: Among a sample of women who were depressed during pregnancy, only 19% had probably moderate to severe depression and nearly half, 48%, reported high maternal confidence in the postpartum period. In the fully adjusted model, women with moderate/severe probable depression showed increased risk of lower maternal confidence in comparison to women without probable depression Prevalence Ratio=1.37 (95% CI 1.10–1.71). CONCLUSIONS: The results reinforce the importance of the evaluation of maternal confidence feelings in primary care particularly for women with more severe forms of depression.